2022
DOI: 10.3390/cancers14092309
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Functional Role of the TRIM8 Protein on Cancer Pathogenesis

Abstract: TRIM/RBCC are a large family of proteins that include more than 80 proteins, most of which act as E3 ligases and catalyze the direct transfer of Ubiquitin, SUMO and ISG15 on specific protein substrates. They are involved in oncogenesis processes and in cellular immunity. On this topic, we focus on TRIM8 and its multiple roles in tumor pathologies. TRIM8 inhibits breast cancer proliferation through the regulation of estrogen signaling. TRIM8 downregulation in glioma is involved in cell proliferation, and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Recent studies on TRIM8 strongly advocate for the critical role of TRIM8 as a regulator of cell proliferation [29] and as an important player in cancer [30], immunity [31], and in ammation [32]. Studies have shown that TRIM8 regulated cell cycle progression and mitosis by affecting cell cycle checkpoints and critical mitotic regulators and indirectly interacts with various motor microtubule-associated proteins (MAPs) such as kinesins [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on TRIM8 strongly advocate for the critical role of TRIM8 as a regulator of cell proliferation [29] and as an important player in cancer [30], immunity [31], and in ammation [32]. Studies have shown that TRIM8 regulated cell cycle progression and mitosis by affecting cell cycle checkpoints and critical mitotic regulators and indirectly interacts with various motor microtubule-associated proteins (MAPs) such as kinesins [33].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, interest in TRIM8 has increased dramatically in recent years. Studies have shown that TRIM8 is critical for the maintenance of genome integrity during cell division and the formation of the mitotic spindle machinery during mitosis [ 78 ]. TRIM8-silenced cells are responsible for a significant portion of the aneuploidy phenotype due to delayed progression through the G2/M phase of the cell cycle associated with centrosome and mitotic spindle abnormalities [ 78 ].…”
Section: Trim8 a Double-edged Sword In Glioblastomamentioning
confidence: 99%
“…Studies have shown that TRIM8 is critical for the maintenance of genome integrity during cell division and the formation of the mitotic spindle machinery during mitosis [ 78 ]. TRIM8-silenced cells are responsible for a significant portion of the aneuploidy phenotype due to delayed progression through the G2/M phase of the cell cycle associated with centrosome and mitotic spindle abnormalities [ 78 ]. TRIM8 regulates cell cycle progression and mitosis by affecting cell cycle checkpoints and critical mitotic regulators and indirectly interacts with various motor microtubule-associated proteins (MAPs) such as kinesins [ 79 ].…”
Section: Trim8 a Double-edged Sword In Glioblastomamentioning
confidence: 99%
“…TRIM8 is involved in conflicting biological processes and exerts regulatory, antiproliferative, anticancer, and pro-inflammatory effects. 31 , 32 Whether TRIM8 has a link with IL-18 and IFN-γ through the signaling pathways mentioned above remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%